PENGARUH CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK - Julfifa Putri S; Triviana Rahmayanti; Sabina Sri Kirana S; Finka Rahmadita (CV. Denasya Smart Publisher, 2024)
Tax avoidance is one way to legally avoid taxes that does not violate tax regulations. Corporate responsibility is a type of commitment to company management, ethical operations, economic development and improving the quality of life of employees and society. The aim of this research is to determine the effect of good governance (audit quality and audit committee) and corporate social responsibility on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research tests the influence of the independent variable, namely. corporate governance and corporate social responsibility on the dependent variable, namely. tax avoidance with a quantitative approach. This research covers four manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique used in this research is the purposive sampling method. The results of this research indicate that good governance (audit quality and audit committee) and corporate social responsibility have a negative effect on tax avoidance.